PERAN HAFALAN TAHFIDZ HADITS MAUDZU'I SANTRI PONDOK PESANTREN ISLAMIC CENTER eLKISI PADA KAFILAH DAKWAH RAMADHAN DI DESA MOJOREJO KECAMATAN PUNGGING KABUPATEN MOJOKERTO - Shafwan, Muhammad Hambal; Umam, Hisbul (STAI Muhammadiyah Paciran Lamongan, 2025)
This research aims to discuss the role of memorizing the tahfidz hadith of Maudzu'i students at the eLKISI Islamic Center Islamic Boarding School in the Ramadhan preaching caravan in Mojorejo village, Pungging sub-district, Mojokerto district.